The effects of maternal alcohol consumption during pregnancy on adverse fetal outcomes among pregnant women attending antenatal care at public health facilities in Gondar town, Northwest Ethiopia: a prospective cohort study - Alemu Earsido Addila; Telake Azale; Yigzaw Kebede Gete; Mezgebu Yitayal (BMC, 2021)
Abstract Background The teratogenic effect of fetal alcohol exposure may lead to actual and potential problems, instantly after birth, at infancy; or even later, and mental impairment in life. This study aimed to investigate the effects of maternal alcohol consumption during pregnancy on adverse fetal outcomes at Gondar town public health facilities, Northwest Ethiopia. Methods A facility-based prospective cohort study was performed among 1778 pregnant women who were booked for antenatal care in selected public health facilities from 29 October 2019 to 7 May 2020 in Gondar town. We used a two-stage random sampling technique to recruit and include participants in the cohort. Data were collected using the Alcohol Use Disorders Identification Test - Consumption (AUDIT-C) standardized and pre-tested questionnaire. Multivariable analysis was performed to examine the association between reported prenatal alcohol exposure (non-hazardous and hazardous) and interested adverse birth outcomes using log-binomial regression modeling. The burden of outcomes was reported using the adjusted risk ratio and population-attributable risk (PAR). Results A total of 1686 pregnant women were included in the analysis, which revealed that the incidences of low birth weight, preterm, and stillbirth were 12.63% (95% CI: 11.12, 14.31), 6.05% (95% CI: 5.00, 7.29) and 4.27% (95% CI: 3.4, 5.35), respectively. Non-hazardous and hazardous alcohol consumption during pregnancy was significantly associated with low birth weight (ARR = 1.50; 95% CI: 1.31, 1.98) and (ARR = 2.34; 95% CI: 1.66, 3.30), respectively. Hazardous alcohol consumption during pregnancy was also significantly associated with preterm birth (ARR = 2.06; 95% CI: 1.21, 3.52). The adjusted PAR of low birth weight related to non-hazardous and hazardous alcohol drinking during pregnancy was 11.72 and 8.44%, respectively. The adjusted PAR of hazardous alcohol consumption was 6.80% for preterm. Conclusions Our findings suggest that there is an increasing risk of adverse birth outcomes, particularly preterm delivery and low birth weight, with increasing levels of alcohol intake. This result showed that the prevention of maternal alcohol use during pregnancy has the potential to reduce low birth weight and preterm birth. Hence, screening women for alcohol use during antenatal care visits and providing advice with rigorous follow-up of women who used alcohol may save the fetus from the potential risks of adverse birth outcomes.